Consecutive Ring-Expansion Reactions for the Iterative Assembly of Medium-Sized Rings and Macrocycles - Stephens, Thomas C.; Unsworth, William P. (Synlett, 2020)
Macrocycles and medium-sized rings have important applications in several scientific fields but can be challenging to make using traditional end-to-end cyclization reactions. Ring-expansion methods represent a useful alternative and offer numerous practical benefits. In this Account, we discuss the current state of the art of ring-expansion strategies that have been applied consecutively. Such methods have the power to expedite the design and synthesis of functionalized macrocycles via the selective, iterative insertion of smaller fragments into ring-enlarged products.1 Introduction2 Insertion Reactions2.1 Transamidation/Transpeptidation2.2 Transesterification2.3 Transthioesterification2.4 Aminyl Radical Cascade2.5 Iterative Synthesis of Lactones2.6 Successive Ring Expansion of β-Ketoesters and Lactams3 Pericyclic Reactions3.1 Sulfur-Mediated Rearrangements3.2 Nitrogen-Mediated Rearrangements4 Fragmentation Reactions5 Conclusions and Future Outlook
Keywords: ring expansion; ring enlargement; rearrangements; macrocycles; medium-sized rings; iterative synthesis